Health outcomes in offspring of mother with breast implants: A protocol of systematic review and meta-analysis. Issue 10 (March 2019) - Song, Ailin; Dang, Jie; He, Zhiyun; Zhang, Youcheng; Liu, Xiaokang; Zhao, Lei; Lv, Xi; Li, Yumin
Abstract: Background: An increasing number of women undergo breast augmentation at their reproductive age. The most existing evidence focuses on the impact of breast implant on the index women's health and breastfeeding after they give birth to a child. No previous systematic review has investigated the association between breast implant in mother and health outcomes in offspring. In this study, we aimed to conduct a systematic review and meta-analysis to evaluate the influence of breast implant on offspring's health outcomes. Methods: A comprehensive search strategy will be conducted including the following databases: MEDLINE (via PubMed), Embase, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, Wan Fang Data. The World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) will be searched as well for retrieving the ongoing studies. The cohort study and case–control study will be considered as eligible study if investigating the impact of breast implant in mother on health outcomes in offspring. The risk of bias of included studies will be appraised by the Newcastle–Ottawa scale. Results: The results of this study will be presented in the full-text of the systematic review. Conclusion: This systematic review and meta-analysis will infer a conclusion on the association between breast implant in mother and health outcomes in offspring, and the quality of existing evidence. PROSPERO registration number: CRD42019121221